Quality and Reliability of YouTube for Patient Information on Neurotoxins - Patel, Manish; Patel, Mit M.; Cristel, Robert T. (Facial Plastic Surgery, 2020)
YouTube is a common source of medical information for patients. This is the first study to assess the reliability and educational value of YouTube videos on neurotoxin procedures. YouTube.com was searched on June 15, 2020 using the keyword “Botox” or “neurotoxin.” A total of 100 videos were reviewed. Sixty-one videos met the inclusion criteria and were included in the final analysis. Video characteristics were noted, and a score was assigned to each video using the Journal of the American Medical Association (JAMA) benchmark criteria and the Global Quality Score (GQS) to measure source reliability and educational value, respectively. A total of 61 videos that met the inclusion criteria had an average length of 589 seconds (9 minutes and 49 seconds), 210,673 views, 5,295 likes, 318 dislikes, and 478 comments. A total of 30 videos (49%) were posted with an intention to educate patients while 31 videos (51%) were posted with the intention to detail a personal experience with neurotoxin. Patient education videos were significantly more reliable (PJAMA< 0.001) and had more educational value (PGQS < 0.001) but were less popular than “personal experience videos.” Personal-experience videos posted by patients had higher popularity, more likes and comments, yet lower scores on reliability and education. Patients will continue to seek educational material online, and clinicians should utilize this information to help primarily educate patients with standardized and accurate information about their treatment.Key Points
Keywords: neurotoxin; youtube; education; quality